2015
DOI: 10.3892/mmr.2015.3988
|View full text |Cite
|
Sign up to set email alerts
|

Association study of C936T polymorphism of the VEGF gene and the C242T polymorphism of the p22phox gene with diabetes mellitus type 2 and distal diabetic polyneuropathy

Abstract: Even with long‑term glycemic control, diabetes mellitus type 2 (DM2) remains the predominant cause of diabetic neuropathy. Single nucleotide polymorphism (SNP) C936T of the vascular endothelial growth factor (VEGF) gene and the SNP C242T of the p22phox (CYBA) gene have been investigated in relation to DM2 and its complications. The aim of the present study was to investigate the association between these two SNPs and DM2, and also between the SNPs and the signs and symptoms of diabetic distal polyneuropathy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…It had been reported that VEGF gene polymorphisms were associated with T2DM, as well as its complications. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that VEGF gene polymorphisms were associated with T2DM, as well as its complications. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…magnesium) are known as macro-metals and are found in high amount in the body tissues, therefore they are also called macro-nutrients. 10 At least 100 mg of each macro-nutrient is required in the daily diet 11 . In contrast, some metals e.g.…”
Section: Discussion:-mentioning
confidence: 99%
“…In the early stages of DPN, abnormalities in the vasa nervorum and loss of nerve fibers can be seen in association with hyperglycemia. Damage to the nervous tissue results in increased intravascular endothelial growth factor ( VEGF ) plasma levels in diabetic animal models [ 52 ]. The ischemia and hypoxia in the nerves of patients with T2D due to microangiopathy of vasa nervorum have always been observed and may be a key pathogenic mechanism of DPN [ 53 ].…”
Section: Other Gene Loci Involved In the Pathogenesis And Prognosmentioning
confidence: 99%
“…The ischemia and hypoxia in the nerves of patients with T2D due to microangiopathy of vasa nervorum have always been observed and may be a key pathogenic mechanism of DPN [ 53 ]. An association study by Ghisleni et al showed a clear association between diabetic polyneuropathy and the C936T polymorphism of the VEGF gene and the C242T polymorphism of the p22phox allele of CYBA gene [ 52 ].…”
Section: Other Gene Loci Involved In the Pathogenesis And Prognosmentioning
confidence: 99%
See 1 more Smart Citation